Personalized Oncology: Organizing Cancer Treatment Around Patient Biology - Julianna Lisziewicz; Oliver Wueseke; Franco Lori (Cancers, 2026)
Clinical guidelines remain the foundation of evidence-based oncology, translating population-derived evidence into treatment recommendations for defined patient groups. However, patients with rare cancers, complex tumor biology, or treatment-refractory disease may reach a point at which applicable evidence is limited, or guideline-recommended treatment options have been exhausted. We propose Personalized Oncology as a complementary framework for treatment selection in these situations. Rather than asking only which treatments benefited similar patients, Personalized Oncology asks which available treatment is expected to provide the most favorable benefit–risk profile for the individual patient. It does so by integrating population-derived medical evidence with patient-specific biological evidence generated from the individual cancer. Importantly, exhaustion of guideline-recommended treatments does not necessarily mean exhaustion of biologically supported treatment opportunities. The supporting evidence, rationale, alternatives, limitations, and uncertainty are documented to enable transparent clinical decision-making. Neither population-derived evidence nor patient-specific biological evidence determines in advance whether an individual patient will benefit. Treatment response must therefore be systematically monitored and incorporated into subsequent decisions. Personalized Oncology standardizes this process while preserving individualized clinical judgment. Systematic capture of each patient’s biology, treatment, and outcome can create a continuous learning framework in which experience from individual patients informs future cancer care.